ChemInform Abstract: Versatile Synthesis of Acylfuranones by Reaction of Acylketenes with α‐Hydroxy Ketones: Application to the One‐Step Multicomponent Synthesis of Cadiolide B and Its Analogues. Issue 45 (14th October 2013) - Peixoto, Philippe Alexandre; Boulange, Agathe; Leleu, Stephane; Franck, Xavier
Abstract Functionalized acylfuranones are prepared in a one‐step procedure by thermal fragmentation of the corresponding dioxinones in the presence of hydroxy ketones under basic conditions.